Tinjauan Yuridis tentang Doktrin Fair Use dalam Undang-Undang Hak Cipta Indonesia dan Implikasinya terhadap Pengembangan Software - Muhammad Habibi; Rohaini; Bayu Sujadmiko (Jurnal Hukum Lex Generalis, 2025)
The application of the fair use doctrine in software development in Indonesia still faces significant challenges, both in terms of regulation and law enforcement. The absence of specific arrangements in the Copyright Law leads to legal uncertainty that can hamper innovation in the technology sector. In the digital era, a balanced copyright policy is needed to support the growth of the creative industry while protecting the rights of creators. This article analyzes the problems of fair use regulation in Indonesia, especially in the context of software development, by comparing it with policies in other countries such as the United States. The results show the need to develop a more detailed evaluation framework to ensure a balance between copyright protection and technological innovation. In addition, education and socialization related to the concept of fair use is a strategic step to increase public understanding and industry players. With policies that support innovation, Indonesia can strengthen its global competitiveness while promoting sustainable economic development.